Korean Guidelines for Diagnosis and Management of Interstitial Lung Diseases: Part 2. Idiopathic Pulmonary Fibrosis - Sang Hoon Lee, M.D.; Yoomi Yeo, M.D.; Tae-Hyung Kim, M.D., Ph.D.; Hong Lyeol Lee, M.D., Ph.D.; Jin Hwa Lee, M.D., Ph.D.; Yong Bum Park, M.D.; Jong Sun Park, M.D., Ph.D.; Yee Hyung Kim, M.D., Ph.D.; Jin Woo Song, M.D., Ph.D.; Byung Woo Jhun, M.D., Ph.D.; Hyun Jung Kim, M.D., Ph.D.; Jinkyeong Park, M.D., Ph.D.; et al. (Tuberculosis and Respiratory Diseases, 2019)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive fibrosing interstitial pneumonia, which presents with a progressive worsening dyspnea, and thus a poor outcome. The members of the Korean Academy of Tuberculosis and Respiratory Diseases as well as the participating members of the Korea Interstitial Lung Disease Study Group drafted this clinical practice guideline for IPF management. This guideline includes a wide range of topics, including the epidemiology, pathogenesis, risk factors, clinical features, diagnosis, treatment, prognosis, and acute exacerbation of IPF in Korea. Additionally, we suggested the PICO for the use of pirfenidone and nintendanib and for lung transplantation for the treatment of patients with IPF through a systemic literature review using experts' help in conducting a meta-analysis. We recommend this guideline to physicians, other health care professionals, and government personnel in Korea, to facilitate the treatment of patients with IPF.